Consumption inequality in urban China, 1995-2013 - Qingjie Xia; Shi Li; Lina Song (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
We use CHIP data from 1995, 2002, and 2013 to investigate inequality in urban household consumption expenditures. Overall inequality in urban household consumption expenditures measured by the Gini coefficient decreased slightly from 0.33 in 1995 to 0.32 in 2002, but it increased to 0.36 in 2013. This followed the same trend as that of urban income, though to a greater extent. However, the percentile ratio of p90/p10 shows that consumption inequality always increased. In addition, basic food consumption inequality was much smaller than overall consumption, with its contribution decreasing from 20 percent in 1995 and 2002 to 14 percent in 2013 and its share decreasing steadily from 34 percent in 1995 to 30 percent in 2002 and further to 24 percent in 2013 as the level of overall consumption moved up in the distribution during each of the three years. Housing consumption inequality was much larger than overall consumption but it was decreasing over time, with its contribution to overall consumption inequality increasing 35 percent in 1995 and 2002 and then to 40 percent in 2013 and its share also sharply increasing from 23 percent in 1995 to 30 percent in 2002 and further to 38 percent in 2013. In addition, its share reveals an upward slope as the level of overall consumption increased in each of the three years.
Keywords: D31; E21; O15; P25; 330; China; urban; consumption; inequality